2021
DOI: 10.1002/mar.21582
|View full text |Cite
|
Sign up to set email alerts
|

Simulated satiation through reality‐enhancing technology

Abstract: We define simulated satiation through reality‐enhancing technology as any attenuation in perceived benefits that occurs within or results from vicarious and simulated intermediary sources. We examine simulated satiation as a factor that underlies consumer experiences with reality‐enhancing technologies and presents nine testable propositions. Each proposition is aimed at determining how simulated satiation can unlock implications in terms of engaging consumers for the right amount of time to improve marketing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 105 publications
(199 reference statements)
2
26
0
Order By: Relevance
“…Supporting customers in product evaluation and enabling them to personally connect with products is vital to forming purchase intentions, and, accordingly, studies have more consistently implied positive effects of AR use on purchase intentions (e.g., Hilken et al, 2017; Poushneh & Vasquez‐Parraga, 2017; see Table 1). In contrast, VR users often find it difficult to evaluate specific products within the holistic virtual environment (e.g., due to “cue overload”), and research thus offers more equivocal results (e.g., Kang et al, 2020; Mishra et al, 2021), demonstrating in some cases that VR diminishes consumption intentions (Deng et al, 2019) due to simulated satiation (Pala et al, 2021). Consequently, we posit:…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…Supporting customers in product evaluation and enabling them to personally connect with products is vital to forming purchase intentions, and, accordingly, studies have more consistently implied positive effects of AR use on purchase intentions (e.g., Hilken et al, 2017; Poushneh & Vasquez‐Parraga, 2017; see Table 1). In contrast, VR users often find it difficult to evaluate specific products within the holistic virtual environment (e.g., due to “cue overload”), and research thus offers more equivocal results (e.g., Kang et al, 2020; Mishra et al, 2021), demonstrating in some cases that VR diminishes consumption intentions (Deng et al, 2019) due to simulated satiation (Pala et al, 2021). Consequently, we posit:…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…During a virtual experience, users draw upon spatial cues to construct mental models of the mediated world to feel "present" within it (Ahn, 2021;Ijsselsteijn & Riva, 2003;Wirth et al, 2007). While telepresence can be induced by all forms of media content, immersive VR displays create vivid telepresence through perceptual inputs, such as 3D vision, spatial audio, and interactive control (Cowan et al, 2021;Jang et al, 2019;Pala et al, 2021;Shin & Biocca, 2018;Tsai et al, 2020). Beyond a spatial presence activated by direct sensory inputs, VR further enhances telepresence by selfreferencing through virtual embodiment of the self (Ahn et al, 2016;Lee, 2004;Shin, 2021) and social presence (Shin, 2013(Shin, , 2017(Shin, , 2018.…”
Section: Telepresence and Transportation In An Immersive Media Experi...mentioning
confidence: 99%
“…marketing (Pala et al, 2021), and retail (Hilken et al, 2021), there has been little consideration of VR in nonprofit fundraising (see Kandaurova & Lee, 2019;Yoo & Drumwright, 2018). UNICEF used VR technologies in 2015 to raise much-needed funds for Syrian refugees (Kang, 2016) by seeking to close the gap between the social and emotional (Yoo & Drumwright, 2018).…”
Section: Charitable Giving and Vrmentioning
confidence: 99%
“…Thus, through the use of VR, different types of land use (e.g., in culturally sensitive surroundings) can be visualized to inform stakeholders and to account for the perception of the landscape by the general public, and to predict the evolution of landscape based on management decisions (Bell, 2001). VR experiences were proposed as a solution to increase simulated satiation (Pala et al, 2021), and has also been shown to align online and offline experiences, which are key in improving attitudes and “form fluent context‐focused mental imagery” (Hilken et al, 2021, p.1).…”
Section: Future Research Agendamentioning
confidence: 99%
See 1 more Smart Citation